Daur al-Tarjamah fi Hiwar al-Ṡaqafat Tarjamah al-Ajnas al-Adabiyyah Anmuzajan - Fouad Larhzizer (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2020)
This article aims at describing the role of translation context of inter-cultural dialogues by tracing it from the translations of literary works. Translation is referred to as transmitting something, i.e. concepts, notions, meanings, from a language to other language. Thus, translating literary works does not only mean changing the language of the works but also transferring the cultures of the society whose language is used in works to other societies. This is because literary works come from, and reflect the cultures of their societies. So, the translations of literary works can be regarded as dialogues among different cultures. Apart from difficulties, translation of literary works with varieties of genres has shown its significant role in creating dialogues among different cultures and civilizations. The process of influencing and being-influenced, particularly between Western literature and Arabic literature has triggered the rise and the development of new genres and features of literature which were absent in any one side. It is here that the literary translation works to transfer moods, mentalities, genius, and models of relationships between different emotions and thoughts.